Hurūf al-ʿAṭf wa Tadrijat al-Tarbiyah Fī Sūrat Luqmān 16-19 (Dirāsat Naḥwīyah) - Ulin Nuha (ALSINATUNA, 2017)
Nahwu was the basic science for understanding the Arabic language especially the holy Quran. There were many investigations of grammatical character. The controversy arises between the scholar interpretation because of this grammatical character. And from this grammatical character, the author want to look at huruf 'athaf and their meanings to the degree of education in surah Luqman 12-19. The author used the library research. The problems were considered ini terms of normative aspect to teach the order of huruf 'athaf in surah Luqman 12-19. He analyzed all the data in a descriptive way and he describe what was mentioned in surah Luqman 12-19. This is also inductive method. In the verses 12-19, There were waw 'athifah used for the unification, fa' 'athifah used for the arrangement and the time limit, summa 'athifah used for the arrangement, au 'athifah used for detail. This research found the teaching method and teaching material with its gradation from Luqman for developing students learning.